Hippocampal blood oxygenation predicts choices about everyday consumer experiences: A deep-learning approach - Chinmai Basavaraj; Martin Reimann; Kobus Barnard; Lynn Nadel (Proceedings of the National Academy of Sciences, 2025)
This research investigates the neurophysiological mechanisms of experiential versus monetary choices under risk. While ventral striatum and insula activity are instrumental in predicting monetary choices, we find that hippocampal activity plays a key role in predicting experiential choices, which we theorize is due to its role in retrieving autobiographical memories. This neurophysiological differentiation clarifies observed variations in risk preferences between experiential and monetary prospects and highlights the importance of domain-specific neurophysiological processes in shaping human decision-making.